Foreign Indebtedness and Economic Growth: Evidence From Sri Lanka - Ravindran, M.; Anandasayanan, S. (Sri Lankan Journal of Business Economics, 2020)
In the sense of the developing world, foreign debts are earned in order to meet the expenses of the government. Consequently, the research aims to assess the effect of foreign debt on economic growth in Sri Lanka using a review of data obtained from the Central Bank of Sri Lanka's annual report for the period 1995 – 2018.The analysis considered international debt as the independent variable, and the dependent variable was the gross domestic product. Labor power, income, and exports were also seen as variables of influence. Based on the results of the pooled standard least squares process, it was found that the foreign debt and economic growth have a substantial negative effect. This explains that the increase in foreign debt of the country would cause in a reduction in economic growth. In respect to control variables, it was found that savings and exports shows a significant impact and labour force does not show any significant impact on economic growth.
Keywords: Foreign Indebtedness; Gross Domestic Product; Economic Growth; Exports; Sri Lanka